1987
DOI: 10.1037/0735-7028.18.3.225
|View full text |Cite
|
Sign up to set email alerts
|

Clinical supervision: An intensive case study.

Abstract: We used a rigorous case study methodology to examine one supervisory dyad's work together during one semester. We used the "best-worst" strategy of several recent researchers, multiple sources of qualitative and quantitative process data, and the perspectives both of the participants and of observers. A number of findings provide hypotheses to guide future research. For example. Session 2 was identified as best by both participants. That it focused on relationship issues between the participants is consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
0
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 28 publications
4
57
0
2
Order By: Relevance
“…Strozier, Kivlighan, and Thoresen (1993) uncovered meaningful sequential relationships between a supervisor's intentions and a trainee's reactions during the course of supervision. Martin, Goodyear, and Newton (1987), combining quantitative measures with a qualitative analysis, compared the trainee's and the supervisor's shared judgment of best and worst sessions. One of their findings was that the participants had similar perceptions of the best sessions, but diverged in their perception of what constituted the worst sessions.…”
mentioning
confidence: 99%
“…Strozier, Kivlighan, and Thoresen (1993) uncovered meaningful sequential relationships between a supervisor's intentions and a trainee's reactions during the course of supervision. Martin, Goodyear, and Newton (1987), combining quantitative measures with a qualitative analysis, compared the trainee's and the supervisor's shared judgment of best and worst sessions. One of their findings was that the participants had similar perceptions of the best sessions, but diverged in their perception of what constituted the worst sessions.…”
mentioning
confidence: 99%
“…In therapeutic settings, research has linked session impact to client improvement (Stiles, Shapiro, & FirthCozens, 1988 and has found session impact ratings to significantly predict termination (Mallinckrodt, 1993). Only one study has been conducted in a supervisory setting (Martin, Goodyear, & Newton, 1987). In that study, session impact was found to vary more for supervisees than for supervisors.…”
Section: Shame-proneness and Session Impactmentioning
confidence: 95%
“…The SEQ developed by Stiles (1980) was initially aimed at measuring dimensions of immediate impacts of a counseling session and later was used to measure immediate impacts of a supervision session (Burke, Goodyear, & Guzzard, 1998;Kivlighan, Angelone & Swafford, 1991;Lichtenberg & Goodyear, 2000;Martin et al, 1987). The SEQ is composed of 21 bipolar adjectives normally rated on a 7-point scale allowing participants to rate how they evaluate their session and how they feel concerning the supervision session.…”
Section: Measures Impactmentioning
confidence: 99%
“…The SEQ has been used in supervision studies and studies of counseling outcomes (Jones & Markos, 1997;Kivlighan, 1989;Martin, Goodyear, & Newton, 1987;Nocita & Stiles, 1986). Tryon (1990) found, for example, that the SEQ Depth score differentiated clients who returned from those who did not return for counseling after the initial session.…”
Section: Instrumentationmentioning
confidence: 98%